Marine predators algorithm for load frequency control of modern interconnected power systems including renewable energy sources and energy storage units - Sobhy, Mohamed A.; Abdelaziz, Almoataz Y.; Hasanien, Hany M.; Ezzat, Mohamed (Ain Shams Engineering Journal, 2021)
Load frequency control (LFC) serves a critical purpose in modern power systems, controlling system frequency and tie-line power flow. Nowadays, the power systems are integrated with an effective contribution of renewable energy sources (RESs). This paper broaches a modern power grid paradigm including conventional generators considering non-linearities, in addition to RESs and energy storage (ES) units for the study of LFC issue. Three forms of RESs are involved in the study, which are wind, photovoltaic and solar thermal. Besides, the system paradigm contains two types of ES units which are superconducting magnetic energy storage (SMES) and battery energy storage (BES). The controllers used for the system model analysis are proportional-integral-derivative (PID) controllers. The optimum design of the controller is established using a novel optimization approach which is a Marine Predators Algorithm (MPA). To certify the realistic credibility of the proposed algorithm, real data are imported to the RESs. The efficacy of the applied MPA-tuned controller is contrasted with that tuned by other competing evolutionary algorithms. The simulation outcomes demonstrate the credibility of the suggested control scheme. Also, the results ensure the role of ES units in enhancing the time-domain transient responses. The simulation findings are acquired through MATLAB framework.